2013
DOI: 10.1074/jbc.m113.509133
|View full text |Cite
|
Sign up to set email alerts
|

LRP1 Assembles Unique Co-receptor Systems to Initiate Cell Signaling in Response to Tissue-type Plasminogen Activator and Myelin-associated Glycoprotein

Abstract: Background: LRP1 is a cell signaling receptor in neurons. Results: LRP1, NMDA receptor, and Trk compose a single system, activating cell signaling in response to tPA and ␣ 2 -macroglobulin. MAG binding to LRP1 recruits p75NTR but not Trk. Conclusion: Ligand-specific co-receptor recruitment explains how LRP1 activates distinct cell signaling pathways in response to different ligands. Significance: Distinct co-receptor assemblies allow LRP1 to regulate the cellular response to its microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
133
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 73 publications
(142 citation statements)
references
References 55 publications
9
133
0
Order By: Relevance
“…In neurons, LRP1 signaling requires the NMDA-R as an essential co-receptor (Bacskai et al, 2000;Qiu et al, 2002;Samson et al, 2008;Martin et al, 2008;Sheng et al, 2008;Mantuano et al, 2013). Other LRP1 co-receptors in neurons include Trk receptors and p75 NTR (Shi et al, 2009;Yoon et al, 2013;Stiles et al, 2013).…”
Section: Nmda-r Is Necessary For Lrp1 Signaling In Schwann Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…In neurons, LRP1 signaling requires the NMDA-R as an essential co-receptor (Bacskai et al, 2000;Qiu et al, 2002;Samson et al, 2008;Martin et al, 2008;Sheng et al, 2008;Mantuano et al, 2013). Other LRP1 co-receptors in neurons include Trk receptors and p75 NTR (Shi et al, 2009;Yoon et al, 2013;Stiles et al, 2013).…”
Section: Nmda-r Is Necessary For Lrp1 Signaling In Schwann Cellsmentioning
confidence: 99%
“…In neurons, tPA can trigger cell signaling through a direct interaction with the NMDA-R, independently of LRP1 (Nicole et al, 2001;Macrez et al, 2010;Ng et al, 2012;Mantuano et al, 2013). To determine whether the NMDA-R signals in response to tPA, independently of LRP1 in Schwann cells, we treated Schwann cells with 12 nM EI-tPA in the presence or absence of RAP for up to 60 min.…”
Section: Nmda-r Is Necessary For Lrp1 Signaling In Schwann Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 In some cases, the recruitment of coreceptors might be necessary for tPA to exert its action. 12 Several studies showed that tPA can promote neurotoxicity, 5,13 especially by an overactivation of NMDARs. 8,11,[14][15][16] However, tPA may also display prosurvival properties on neurons and oligodendrocytes 4,6,[17][18][19][20] involving either an EGFR-dependent signaling, 6 binding to Annexin-II 18 or active NMDARs.…”
mentioning
confidence: 99%